(untitled) (International relations and international law Journal, 2016)
This article is concerned to analyze the conceptions of origin and expansion of transnational corporations. The goal of this study is to examine their activities on the eve of XXI century in relation to process of globalization. Process of Globalization of the last decade contributes to alteration of the system of World Order: the character of relationship between subjects of the World Policy is changing, the role oftraditional actors is coming down, new forms of supranational structures are springing up. In these process transnational corporations plays the main role, which are the cause and the consequence of globalization. Based on current tendences of relations of TNCs with nation states, the author argues that transnational corporations deviate even more from controlby States.